2017
DOI: 10.1093/hmg/ddx179
|View full text |Cite
|
Sign up to set email alerts
|

Vps35 in cooperation with LRRK2 regulates synaptic vesicle endocytosis through the endosomal pathway in Drosophila

Abstract: Mutations of the retromer component Vps35 and endosomal kinase LRRK2 are linked to autosomal dominant forms of familial Parkinson's disease (PD). However, the physiological and pathological roles of Vps35 and LRRK2 in neuronal functions are poorly understood. Here, we demonstrated that the loss of Drosophila Vps35 (dVps35) affects synaptic vesicle recycling, dopaminergic synaptic release and sleep behavior associated with dopaminergic activity, which is rescued by the expression of wild-type dVps35 but not the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 52 publications
13
111
1
Order By: Relevance
“…In addition, variation in genes that encode core components of the autophagic machinery, the proteins Atg5 and Atg7, is reported risk factors for PD (Chen et al, 2013a, 2013b). Lastly, recent work also found that variation in the EndoA1 gene constitutes a risk factor for PD (Chang et al, 2017). We and others showed that EndoA plays a prominent role in synaptic autophagy in fruit flies and mice (Murdoch et al, 2016;Soukup et al, 2016).…”
Section: Macroautophagy and Mitophagymentioning
confidence: 53%
See 1 more Smart Citation
“…In addition, variation in genes that encode core components of the autophagic machinery, the proteins Atg5 and Atg7, is reported risk factors for PD (Chen et al, 2013a, 2013b). Lastly, recent work also found that variation in the EndoA1 gene constitutes a risk factor for PD (Chang et al, 2017). We and others showed that EndoA plays a prominent role in synaptic autophagy in fruit flies and mice (Murdoch et al, 2016;Soukup et al, 2016).…”
Section: Macroautophagy and Mitophagymentioning
confidence: 53%
“…EndoA is emerging as a central nexus of synaptic biology in the context of PD. Not only is EndoA phosphorylated by LRRK2, but the protein also binds to Parkin and Synj1 (Schuske et al, 2003;Verstreken et al, 2003;Trempe et al, 2009;Cao et al, 2014;Fig 2) and variation at the EndoA1 locus (SH3GL2) is a risk factor for PD (Chang et al, 2017). Mutations in either parkin or SYNJ1 cause an autosomal-recessive early-onset form of PD, and mutations in Synj1 are in general more severe (Krebs et al, 2013;Quadri et al, 2013;Olgiati et al, 2014;Kirola et al, 2016).…”
Section: Endoamentioning
confidence: 99%
“…To explore the requirement of retromer at synapses, we next turned to the larval neuromuscular junction (NMJ). Based on previous work, Vps35 is present at both the NMJ pre-and post-synapse, and loss of Vps35 causes synaptic terminal overgrowth and altered neurophysiology suggestive of synaptic vesicle recycling defects (Inoshita et al, 2017;Korolchuk et al, 2007;Malik et al, 2015;Walsh et al, 2019). We therefore examined whether Vps29 mutants show similar phenotypes.…”
Section: Retromer Regulates Synaptic Vesicle Endocytosis and Recyclingmentioning
confidence: 99%
“…Originally discovered in the yeast S. cerevisiae (Seaman et al, 1998), the heterotrimeric core proteins of the retromer, VPS35, VPS26, and VPS29, are highly conserved among eukaryotes (Koumandou et al, 2011). Retromer components are broadly expressed, including in the invertebrate nervous system (Inoshita et al, 2017;Wang et al, 2014) and throughout the mammalian brain (Appel et al, 2018;Tsika et al, 2014). In murine neurons, retromer is present in both axons and dendrites, and at the synapse (Munsie et al, 2015;Tsika et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation